Assessing Moisture Resilience of Wall Assemblies to Wind-Driven Rain Loads Arising from Climate Change - Xiao, Zhe (Université d'Ottawa / University of Ottawa, 2022)
Moisture loads arising from the deposition of wind-driven rain (WDR) on building façades can induce detrimental effects to wall assembly components and can adversely influence their long-term performance. Wind-driven rain as a climatic phenomenon will inevitably be affected by the evident changing climate in the near future. Wall assemblies subjected to wind-driven rain loads will also perform differently due to a varying moisture environment over the course of time. The performance of the building envelope, including the wall assembly, largely determines the serviceability of a building over its life cycle. Thus, it is essential for practitioners to understand and to be able to assess such performance. In this study, a complete procedure has been developed to permit assessing the moisture resilience of wall assemblies to wind-driven rain loads arising from climate change. The development of this procedure included four phases. In the first phase the historical and projected climate data was analysed to identify the possible wind-driven rain conditions to which a wall assembly may be exposed. The magnitudes of wind-driven rain and driving-rain-wind-pressure for different return periods were also investigated. Based on the results from phase one, a watertightness test protocol was established taking into consideration the possible ranges of wind-driven rain and driving-rain-wind-pressure as they may occur spatially, as well as temporally, across Canada. The range of watertightness test parameters was accommodated in the newly built Dynamic Wind and Wall Testing Facility (DWTF) at the National Research Council Canada. Thereafter in phase two of the research, wall assemblies having different configurations were tested in the DWTF following the test protocol to obtain the moisture load for wall assemblies under different wind-driven rain conditions. Such moisture loads were formulized and used in the third phase, where hygrothermal simulations were conducted to derive the hygrothermal parameters of the wall assemblies subjected to historical and projected climate data. In the final research development phase, different criteria and methods were explored to describe the performance of wall assemblies based on the hygrothermal parameters. During the development of the moisture resilience assessment procedure, a novel wind-driven-rain-pressure-index was devised to describe the extent of the effects arising from the concurrent action of wind-driven rain and driving-rain-wind-pressure loads on a vertical wall assembly; a new two-step approach was established to formulize the watertightness test results and thereby permit calculating the moisture load using values of hourly wind-driven-rain and hourly driving-rain-wind-pressure of a given location; a novel severity index was proposed to quantitatively describe the damage events arising from such moisture load on the wall assemblies. The moisture performance of tested wall assemblies subjected to historical and projected future climate were compared and discussed. The risks of occurrence of damage events in wall assemblies during different time periods were also demonstrated.
Keywords: Climate change; driving-rain-wind-pressure; hygrothermal simulation; moisture load; risk analysis; watertightness test; wind-driving rain; wood frame wall assembly